L’industrie de l’assurance de personnes au Canada - Duhaime, Guy (Assurances)

(untitled) (HEC Montréal, 1995)
The following paper was presented by l'Association des intermédiaires en assurance de personnes du Québec before the Senate Banking Committee on September 28, 1994. Mr. Guy Duhaime, President of the Association, describes the mandate of the AIAPQ, then highlights some of the consequences resulting from the collapse of Toronto-based Confederation, the country' s biggest-ever insurance company failure. New rules are needed for the legitimate protection of insureds. These include, maintaining the link between the insured and the intermediaries after settlement in bankruptcy proceedings and restricting the selling of insurance by banking institutions except when such institutions are subject to the same rules as insurance intermediaries.